Implementation of Motorcycle Rental Information System at the Trans Jaya Tangerang - Aditya Setiawan; Reza Avrizal; Risma Nurul Auliya (SYSTEMATICS, 2020)
The growth in science and technology is accelerating, resulting in a competition that is becoming more intense. Advanced science and technology are obviously also in contact with computers. Computer use can minimize potential errors in data processing compared with manual data processing. The development of these sciences and technologies also encourages companies to improve corporate performance, and one of their uses is the creation of the information systems that companies need. The purpose of this study is to design and build a desktop java-based motorbike rental information system for Koperasi Trans Jaya Tangerang. The methodology used by researchers was grounded research. The methods of data collection used in this study are interviews, observations, and library studies.